Collins Cobuild key words for IELTS. (Nxb. Tổng hợp Tp.HCM : Nhân Trí Việt, 2012)
Introductio; Pronunciation guide; Guide to entries; Guide to grammatical labels; Word lists; Sciences; Social sciences; Arts; Multi-discipline; Academic study; Academic word list; Key words A-Z.